Testing and modelling creep compression of waste rocks for backfill with different lithologies. (January 2020) - Li, Meng; Zhang, Jixiong; Meng, Guohao; Gao, Yuan; Li, Ailing
Abstract: To investigate the behaviours of the creep compression of waste rocks used for backfill, a load testing system for granular backfill materials is developed in this paper and tests are conducted on creep compression under stepwise loading by using waste rocks for backfill. The results show that the waste rocks for backfill exhibited prominent creep compression behaviours, where the creep curve was non-linear. At a certain applied stress, creep occurred at an attenuated rate, and steady-state creep occurred at a zero rate only in waste rocks used for backfill. At high stress, the samples exhibited creep at an attenuated rate and steady-state creep at a non-zero rate. Based on fractional-order calculus, a fractional-order Abel dashpot is proposed to replace the Newtonian dashpot in the conventional Burgers' model. Using this, a Maxwell–Kelvin (NMK) model is proposed to describe behaviours of the creep compression of waste rocks used for backfill, and a 3D creep equation for the aforementioned NMK model is deduced. In addition, according to the results of creep compression tests on waste rocks used for backfill, the inversion and identification of parameters in the NMK model were carried out using the 1stOpt software. Comparisons of the fitted and the test data showed that they coincided, thus verifying the rationality of the NMK model.